Sensitivity of Band-Pass Filters with Arithmetic Symmetry - A. V. Bondarenko; V. V. Reznichenko; А. V. Kurkov; V. P. Demidov; V. I. Mozhar (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2008)
The paper considers an analytical method for calculation of sensitivity of band-pass filters that have high dimensionality with arithmetic symmetry of amplitude-frequency characteristic while changing one or several parameters.